Study on the Motion Law of Logarithmic Spiral Type Cam Mechanism - Yin Libin; Fu Lihua; Zhao Yan; Song Hua; Gao Jingjun (Jixie chuandong)
The solid models of the logarithmic spiral cam mechanism and common cam mechanism are established by using SolidWorks,and the kinematics simulation is carried out.Then,by using the software of ANSYS / LS-DYNA,the dynamics analysis of the two kinds of cam mechanism is carried out,and the variation situation of the maximum stress of cam mechanism and the follower changing with time is obtained.By contrast analysis between the dynamics simulation and the kinematical simulation of logarithmic spiral cam mechanism and common cam mechanism,find that the logarithmic spiral cam mechanism drive is more steady during the operation,and the force variation and the average stress of cam and follower are lower,which indicates that the logarithmic spiral cam mechanism is superior to common cam mechanism,and possessed of popularization and application value.